Karakteristik Struktur Mikro Komposit Aspal Silika Sekam Padi Dengan Variasi Komposisi (20%:80%, 15%:85% dan 10%:90%) - Qori Sari Dewi; Simon Sembiring; Syafriadi Syafriadi; Ediman Ginting (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Synthesis and characterization of rice husk and asphalt silica composites with various compositions have been carried out 20%: 80%, 15%: 85% and 10%: 90%. Silica synthesis from rice husk wa carried out using the sol-gel method. The materials used are rice husks, solid asphalt, distilled water, gasoline, NaOH and HNO3. This research was conducted of variations in the composition the effect of silica and asphalt on the microstructure and structure of the sample. The characterization results of Scanning Electron Microscopy and Energy Dispersive Spectroscopy (SEM-EDS) on the surface of silica asphalt composites in the form of erratic clots and cracks on the surface of the sample with an average grain size of 3.483 µm, 8,127 µm, and 7,192 µm. The analysis EDS results in the elements content contained in the sample elements of carbon (C), silicon (Si), oxygen (O), a little element of sulfur (S) and aluminum (Al). Then, the results of the X-Ray Diffraction (XRD) characterization obtained the structure of amorphous silica and amorphous carbon.